Ability of cash flow patterns to predict occurrence of financial distress / Adriana Shamsudin - Shamsudin, Adriana (2014)
A relatively simple and convenient way to analyse a company’s financial status is to examine the patterns of cash flow. The cash flow patterns derived from positive and negative signs of its cash flow components that consist of operating, investing and financing activities. The present study investigated eight types of cash flow patterns to predict financial distress incidence. The data collected consists of 62 distressed and 62 healthy companies within the context of Malaysian public listed companies for three years prior distress year between 2006 until 2013. The primary aim of the present study is to examine whether there is any significant relationship between patterns of cash flow components and financially distress companies. The results revealed that the patterns that can be predictor of financial distress incidence are the second (+ - -), third (+ + -), fourth (+ - +) and eighth (---- ) cash flow patterns. The results also found that there is a significant difference between distressed and healthy companies in incidence of different patterns of cash flow. In addition, in one year before distressed, the most popular patterns among distressed companies in Malaysia are second (+ - -) and third (+ + -) type of cash flow pattern. For two and three years before distressed, the most frequent pattern is also the second (+ - -) type of cash flow pattern followed by sixth (- - +) cash flow pattern. Therefore, patterns of cash flow can be considered as an alternative tool to predict the occurrence of financial distress. The results provide an insight to the investors that this is another warning sign of impending bankruptcy.